2011
DOI: 10.1074/jbc.m111.222760
|View full text |Cite
|
Sign up to set email alerts
|

Usp18 Regulates Epidermal Growth Factor (EGF) Receptor Expression and Cancer Cell Survival via MicroRNA-7

Abstract: Epidermal growth factor receptor (EGFR) is involved in development and progression of many human cancers. We have previously demonstrated that the ubiquitin-specific peptidase Usp18 (Ubp43) is a potent regulator of EGFR protein expression. Here we report that the 3-untranslated region (3-UTR) of the EGFR message modulates RNA translation following cell treatment with Usp18 siRNA, suggesting microRNA as a possible mediator. Given earlier evidence of EGFR regulation by the microRNA miR-7, we assessed whether miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 51 publications
3
57
0
Order By: Relevance
“…The current results support the suggestion that USP18 might be linked to the innate immune response to viruses and USP18 gene down-regulation, which results in an increased antiviral activity against many kinds of viruses 39. Interestingly, USP18 probably has oncogenic properties, and its inhibition may have possibilities for cancer therapeutics 40. Cohort studies have indicated that prevention and cessation of smoking are the most important determinants of lung, head and neck cancer 41,42.…”
Section: Discussionsupporting
confidence: 82%
“…The current results support the suggestion that USP18 might be linked to the innate immune response to viruses and USP18 gene down-regulation, which results in an increased antiviral activity against many kinds of viruses 39. Interestingly, USP18 probably has oncogenic properties, and its inhibition may have possibilities for cancer therapeutics 40. Cohort studies have indicated that prevention and cessation of smoking are the most important determinants of lung, head and neck cancer 41,42.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it is tempting to speculate that activation of this pathway might be established in Trim24 KO HCC to circumvent IFN/STAT antitumoral activity. Moreover, Usp18 has been recently demonstrated to enhance epidermal growth factor receptor (EGFR) mRNA translation, thus promoting tumorigenic activity, cancer cell survival, and cell proliferation (53). This discovery hence makes Usp18 an interesting candidate for mediating IFN/STAT-induced hepatocarcinogenesis in Trim24 KO mice.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, HnrnpK might be a direct mediator of the pro-viral Isg15 effect in HCV replication. Moreover, it has been shown that HnrnpK expression is enhanced by knockdown of the Isg15 protease USP18 (Duex et al, 2011). Another group has shown the USP18 knockdown results in increased ISG15 expression (Murray et al, 2011).…”
Section: Discussionmentioning
confidence: 98%